(untitled) (R&D Journal, 2024)
A short overview of the application of schlieren and shadowgraph image construction has been presented, focusing on its use in interpreting compressible CFD data. Numerical flow visualisation methods have beenused for the validation of numerical models of real flow fields but are also a valuable tool for identifying and interpreting flow field features and provide a useful means for extracting information from the numerical data that may not be readily apparent.